Determination of antifungal effect of natural oil and synthetic gutta percha solvents against candida albicans: A disc diffusion assay - Smita D Dutta (Journal of Pharmacy and Bioallied Sciences, 2023)
Introduction: The practice of removing root canal fillings with solvent materials is frequently required to help an irrigation solution enter the tubules. The current research was aimed at assessing the antifungal properties specifically the candida albicans of the various solvent materials used for the gutta-percha (GP) material. Materials and Methods: Current research was aimed at as a lab method using the disk diffusion technique where the zone of inhibition (ZOI) was calculated. The materials that were analyzed were: orange oil, xylene, turpentine oil, chloroform, and eucalyptus oil. Candida albicans was the test organism employed in the investigation. The agar plates were covered with approximately 500 μL of the suspension. The sterile and empty disks were impregnated with 10 μL of pure GP solvents. These plates were incubated for one day at room temperature. The ZOI's mean diameters were calculated for all five materials and quantified each solvent's fungicidal activity. For intergroup comparison, ANOVA was utilized. P values < 0.05 were deemed substantial. Results: The maximum inhibition exhibited by the Eucalyptus Oil it was 19.01 ± 1.02 mm. This was followed by Xylene. The other three solvents Chloroform, Orange Oil, and Turpentine Oil exhibited a similar ZOI. When all the solvents were compared there was a significant variance of P < 0.001. However, there were significant variances for the Eucalyptus Oil and the Xylene to all the other solvents P < 0.001. Conclusion: This investigation showed that, in comparison to other solvents, the use of eucalyptus oil considerably reduced the levels of Candida Albicans.